A tale of two cities - Dickens, Charles (Wordsworth Editions Hertfordshire [England], 2011)
Traces the private lives of a group of people caught up in the cataclysm of the French Revolution and the Terror. The author based his historical detail on Carlyle's "The French Revolution", and his own observations and investigations during his numerous visits to Paris